Diffusion coefficients of sodium dodecylsulfate in aqueous solutions of sucrose and in aqueous solutions - Ribeiro, Ana C. F. (2001)
Differential diffusion coefficients of sodium dodecylsulfate (SDS) in aqueous solutions of sucrose and in aqueous solutions at 298.15 K, over the concentration range 0.0018 M to 0.0817 M, have been measured using a conductimetric cell and an automatic apparatus to follow the diffusion. The results are discussed on the basis of the Onsager-Fuoss model. The cell uses an open ended capillary method, while a conductimetric technique is used to follow the diffusion process by measuring the resistance of a solution inside the capillaries, at recorded times. The influence of molecules of sucrose on the diffusion of this electrolyte was investigated. The presence of sucrose increases the diffusion coefficients of sodium dodecylsulfate both above and below the critical micelle concentration (cmc) of the surfactant.